Impact of Safety Leadership and Employee Morale on Safety Performance: The Moderating Role of Harmonious Safety Passion - Emhemed Slil; Kolawole Iyiola; Ahmad Alzubi; Hasan Yousef Aljuhmani (Buildings)
Construction sites are among the most hazardous workplaces, making safety a critical concern in the sector. This study investigates the interplay between safety leadership, employee morale, harmonious safety passion, and safety performance through the lens of the social exchange theory. This research aims to assess how safety leadership impacts safety performance directly and indirectly, with employee morale acting as a mediator while harmonious safety passion moderates these relationships. A quantitative approach was employed, with data collected through structured questionnaires administered to construction workers in Istanbul and Ankara, Turkey. A total of 438 valid responses were analyzed using the Statistical Package for the Social Sciences (version 25) and Analysis of Moment Structures (version 24) for reliability, validity, and hypothesis testing. The findings confirm that safety leadership positively influences both safety performance and employee morale. Employees with high morale directly contribute to improved safety performance and act as a mediator between safety leadership and safety performance. Additionally, harmonious safety passion moderates the relationship between employee morale and safety performance, strengthening the link for workers with higher levels of passion. However, its moderating effect on the relationship between safety leadership and safety performance was not significant. These insights offer practical implications for designing safety training programs, leadership development initiatives, and policies aimed at improving safety outcomes in construction. Future research should explore longitudinal designs and diverse contexts to further validate these findings.